Antimicrobial Activity of Eco-enzymes with Various Dilutions As A Natural Disinfectant - Najla Lubis; Rizki Damayanti; Sheila Wardani (Jurnal Penelitian Pendidikan IPA, 2025)
Ecoenzyme perfectly utilizes biological waste for non-chemical sanitation products through the fermentation of sugar, organic materials, and water. Ecoenzyme has been used to inhibit the growth of bacteria such as Staphylococcus aureus and Propionibacterium acnes. This study aims to determine the optimum concentration of eco enzyme as a natural antibacterial and disinfectant. This method uses gram-positive bacteria Staphylococcus aureus and gram-negative bacteria Escherichia Coli with the disc method. The dilution variations used were 0, 1:10, 1:50, and 1:100. Ecoenzyme is made from organic materials from pineapple, orange, papaya, starfruit, quinine, and mango skin waste (Bioz1), and coenzyme from pineapple, orange, banana stem, noni, quinine waste (Bioz2). The results showed that a ratio of 1:10 was the most effective dilution variation for inhibition against both types of bacteria. Furthermore, dilution at this concentration can be used as a natural disinfectant. The presence of acetic acid and enzymes (i.e. lipase and amylase) can inhibit certain strains of microorganisms, namely Escherichia coli and Enterococcus sp.